Allografts in PCL reconstructions - Silva, L. D. (2013)
Posterior cruciate ligament (PCL) injuries are often associated with other ligament lesions. Multiligament reconstructions require an important quantity of grafts and often determine the need for cadaver allografts during the surgical repair procedures. Herein, the fundamentals of allografts that have been currently used for PCL reconstructions are overviewed. The main issues to be considered when surgeons choose this therapeutic option are also discussed.